Contribution of temperature and thickness in the hyperfine magnetic field of W(110)/Fe(110)/Ag thin films - Fayez طارق محمد; Saleh ابراهيم عبدالحفيظ; Ahmad مصططفى محمد (Journal of Pure & Applied Sciences, 2021)
The temperature size effects are predicated in framework of different hypothesis such as isotropic spin wave theory, which depends on magnetic excitation of the spin system, while the microscopic approach of magnetization is related to the local magnetization of the system. In Bloch's formula at low temperatures, Heisenberg's model was relied upon to describe the Magnetic hyperfine field Bhf with the presence of the parameters: ground-state magnetic hyperfine field Bhf(0) and spin wave parameter b, and, in thin films in the case of probe monolayer, these parameters depend on the thickness of the film and the position of the probe layer. In order to explain the parameters b and Bhf(0) that control the effects of size on the magnetization of thin films, which is the case in which the finite thickness of the sample also affects the Bhf, the following points were focused on: First, changes in the finite thickness of the sample in order to study the effect of size. Second, because of the electronic interaction around the surface/interface area, the effect of the lower layer (substrate/probe monolayer interface) was distinguished from the effect of the coating material (probe monolayer/noble metal) in order to study the effect of the surface. A model was found describing the behavior of the Magnetic hyperfine field in these cases, which differed from the Bloch formula with distinct values called (g1,g2,g3,g4), and one of them was identified as g1, which is the Fermi contact field Bhf,cp, and by means of these values, the parameters b and Bhf(0) were defined for the different layers, which are considered the basis of research in the subjects of local thermal excitation and their dependence on thickness.